1990
DOI: 10.1016/0014-5793(90)80041-g
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)‐coproporphyrin I as a photoactivable group in sequence‐specific modification of nucleic acids by oligonucleotide derivatives

Abstract: The 34-mer oligodeoxynucleotide was shown to be selectively modified at the G17 position upon photoirradiation in the presence of complementary 17-mer oligodeoxynucleotide bearing Pd(II)-coproporphyrin I covalently linked to the S-end phosphate group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Similar results in sensitized photomodification of nucleic acids were obtained earlier with conjugates containing other reactive groups, including porphyrins and their analogs, such as Pd(II)-coproporphyrin I [20], chlorine [21], sapphyrin, and Dy(III) texaphyrin [22]. Using oligonucleotide tags, it is possible to target the reagent to the required nucleic acid sequence, thus enhancing the selectivity of the process.…”
Section: Discussionsupporting
confidence: 61%
“…Similar results in sensitized photomodification of nucleic acids were obtained earlier with conjugates containing other reactive groups, including porphyrins and their analogs, such as Pd(II)-coproporphyrin I [20], chlorine [21], sapphyrin, and Dy(III) texaphyrin [22]. Using oligonucleotide tags, it is possible to target the reagent to the required nucleic acid sequence, thus enhancing the selectivity of the process.…”
Section: Discussionsupporting
confidence: 61%
“…An early work (Fedorova et al, 1990) on a Pd(II)-coproporphyrin I conjugated to a 17-mer DNA reported on the selective photocleavage of a complementary DNA sequence after irradiation at 330-410 nm. Photogenerated crosslink products were detected, which were further treated with hot piperidine to reveal specific oxidation of guanine in close proximity to the dye.…”
Section: Metal Complexes Based On Porphyrin-like Ligands As Chromophoresmentioning
confidence: 99%
“…Many of the applications where porphyrins are used as molecular probes in aqueous media (fluorescent probes [1,2], phosphorescent probes [3][4][5][6], photosensitizing probes [7][8][9][10], chemiluminescent catalysts [11]) require the possibility for a site-specific attachment of the probe to a target molecule. A prerequisite for such site-specific attachment (later: labeling) is that the probe molecule includes a single chemical functional group of a kind (later: monosubstituted) which can be selectively reacted with a chemical group present in the target molecule.…”
Section: Introductionmentioning
confidence: 99%